2020
DOI: 10.1039/d0an00591f
|View full text |Cite
|
Sign up to set email alerts
|

A tetrahedral DNA nanostructure-decorated electrochemical platform for simple and ultrasensitive EGFR genotyping of plasma ctDNA

Abstract: In this study, we propose an on-site electrochemical platform for sensitive simultaneous genotyping of the two major EGFR mutations (19del and L858R) through plasma ctDNA based on tetrahedral DNA nanostructure decorated screen-printed electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…As reported in the literature, the DNA origami triangles, stored at 4 °C in low-salt buffers, were stable for 2 months . The tetrahedral DNA nanostructure-decorated electrochemical platform, stored at 4 °C, remained stable for 7 days . Positive attempts were made to improve the stability of the DNA nanostructures in some studies.…”
Section: Results and Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…As reported in the literature, the DNA origami triangles, stored at 4 °C in low-salt buffers, were stable for 2 months . The tetrahedral DNA nanostructure-decorated electrochemical platform, stored at 4 °C, remained stable for 7 days . Positive attempts were made to improve the stability of the DNA nanostructures in some studies.…”
Section: Results and Discussionmentioning
confidence: 64%
“…16 The tetrahedral DNA nanostructure-decorated electrochemical platform, stored at 4 °C, remained stable for 7 days. 31 Positive attempts were made to improve the stability of the DNA nanostructures in some studies. The robust 6-helix DNA tile tube was built using a topological structure.…”
Section: Resultsmentioning
confidence: 99%
“…EC assays often involve PCR amplification of the DNA fragment where the mutation site is present, followed by a specific capture of the amplicons by a mutation-specific probe. This was shown, for instance, for point mutations in TP53 [75], KRAS [74], EGFR [69,70,105], or BRCA1 genes [68]. For example, Xu et al reported EC biosensor that analyzes in-frame deletions in exon 19 of an EGFR gene [69].…”
Section: Pcr-based Ec Biosensorsmentioning
confidence: 99%
“…Our previous work has also proposed an on-site electrochemical platform for the sensitive simultaneous genotyping of the two major EGFR mutations (19del and L858R) through plasma ctDNA based on TDN-decorated SPGE. 95 As shown in Fig. 5B, Linear-After-The-Exponential (LATE)-PCR combined with amplification refractory mutation system (ARMS) was adopted to produce abundant biotin-labeled single-stranded DNA with high amplification efficiency and specificity.…”
Section: Spe Modified With Functional Dna Nanostructuresmentioning
confidence: 99%